2006
DOI: 10.2514/1.18915
|View full text |Cite
|
Sign up to set email alerts
|

CFD/CSD Prediction of Rotor Vibratory Loads in High-Speed Flight

Abstract: A computational fluid dynamics (CFD) model is coupled with a computational structural dynamics (CSD) model to improve prediction of helicopter rotor vibratory loads in high-speed flight. The two key problems of articulated rotor aeromechanics in high-speed flight-advancing blade lift phase, and underprediction of pitch link load-are satisfactorily resolved for the UH-60A rotor. The physics of aerodynamics and structural dynamics is first isolated from the coupled aeroelastic problem. The structural and aerodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 23 publications
(18 reference statements)
2
41
0
Order By: Relevance
“…To overcome these limitations, recent studies have utilized computational fluid dynamics (CFD) methods based on the Euler and Navier-Stokes equations. However, most applications of the CFD methods were limited to isolated-rotors (Ananthan et al, 2008;Datta et al, 2006;Potsdam et al, 2004;Yang et al, 2002) and rotor-fuselage configurations (Dietz et al, 2008;Nam et al, 2006;Yang et al, 2008;You et al, 2006). Therefore, important features of the aerodynamic interaction of complete helicopter configurations are still not well understood.…”
Section: Kwonetal Numerical Investigation Of Aerodynamic Interferenmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, recent studies have utilized computational fluid dynamics (CFD) methods based on the Euler and Navier-Stokes equations. However, most applications of the CFD methods were limited to isolated-rotors (Ananthan et al, 2008;Datta et al, 2006;Potsdam et al, 2004;Yang et al, 2002) and rotor-fuselage configurations (Dietz et al, 2008;Nam et al, 2006;Yang et al, 2008;You et al, 2006). Therefore, important features of the aerodynamic interaction of complete helicopter configurations are still not well understood.…”
Section: Kwonetal Numerical Investigation Of Aerodynamic Interferenmentioning
confidence: 99%
“…The flight conditions cover level flights and transient maneuvers, and the measured data included aerodynamic pressures, structural loads, control positions, and rotor forces and moments. This extensive database (Bousman et al, 2005) was widely used for validating helicopter aerodynamic analysis tools (Ananthan et al, 2008;Bousman, 2009;Bousman and National Aeronautics and Space Administration Moffett Field CA Ames Research Center, 2003;Datta et al, 2006;Howlett, 1981;Potsdam et al, 2004;Yeo et al, 2002). In the present study, two level flight cases, C8534 and C8513, were selected.…”
Section: Uh-60a Configurationmentioning
confidence: 99%
“…The periodic blade deformations obtained from this run are transferred to the CFD solver using a fluid-structure interface. The CFD solver deforms the blade mesh and computes the periodic airloads, which is subsequently transferred to the structural dynamics system using the delta airloads method, explained in detail in [5][6][7][8]. The delta airloads are first recast in a shaft-fixed frame as three components of forces and moments at each radial location before its use in the CSD analysis.…”
Section: Computational Methods and Validation Studiesmentioning
confidence: 99%
“…They found that the predictions were sensitive to the particular wake model used and the trim state. Datta and Chopra also attempted to couple the helicopter structural dynamics model in UMARC with a separate computational fluid dynamics (CFD) analysis to predict the vibratory loads in a high-speed flight [11]. They reported that CFD and computational structural dynamics (CSD) coupling improved the prediction for torsional loads.…”
mentioning
confidence: 99%